Psychological and social variables affecting cancer diseases - Hani, Salwa Mohammed (Al-Adab Journal, 2015)
Find goal : to identify the Alnevsyah and social factors associated with developing cancer , and try to put the policy of social and psychological care for cancer patients . Research importance: To study the first Ahmetin community scientific and second former is the impact of cancer on family and social life for cancer patients also accompanied by psychological changes affect the patient one way or another, which represents an importance in the study of this problem in terms of disclosure of the associated rate of cancer factors which benefits from cancer patients and those around him and can help to address the social and psychological problems that surround cancer patients. Also, the study of social and psychological factors associated with the cancer benefit social and psychological disciplines relevant medical side, which helps to visualize or method of dealing with socially and psychologically cancer patients.The scientific importance , is represented studying the social and psychological factors associated with cancer patients in addition to the Heritage on health and disease , especially if this intervention study in the field of inter -disciplinary ( psychosocial ) Research Methodology : adopted Find the sample survey method either search tool Vtmthelt depending on the form of a questionnaire as a key tool for Bges.mtdmna (49) question some baseline data and other private research topic Alasasa.ama study sample size was reached ( 200 ) Single distributed on the basis of cultural background ( Houdrah- rural ) as the number of urban ( 120 ) and Alriqian (80) . Find treatment center in chemical Eldemerdash Hospital in Cairo was conducted. The research found significant results showed the impact of psychological and social factors in cancer diseases that built the need to pay attention to it by the concerned state institutions and citizens